2018
DOI: 10.1007/s40262-018-0663-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ADS-5102 (Amantadine) Extended Release Capsules Administered Once Daily at Bedtime for the Treatment of Dyskinesia

Abstract: Background Preclinical and clinical studies suggest amantadine immediate-release (IR) may reduce dyskinesia in Parkinson's disease (PD), although higher doses are associated with increased CNS adverse events (AEs). ADS-5102 is an extended release amantadine capsule formulation, designed for once-daily dosing at bedtime (qhs) to provide high concentrations upon waking and throughout the day, with lower concentrations in the evening. The pharmacokinetics (PK) of ADS-5102 were assessed in two phase I studies in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Improvements in continuous delivery of amantadine would provide a smooth PK profile achieving high concentrations and better coverage throughout the day compared with the peaks and troughs associated with bolus dosing. As reported in the study by Hauser et al (2018), ADS-5102 can be dosed once daily at bedtime to achieve high morning and sustained daytime amantadine plasma concentrations when symptoms of dyskinesia occur. PK modeling suggested the recommended daily ADS-5102 dosage (274 mg once daily at bedtime) provided maximum steady-state concentrations of ∼1500 ng/ml in patients with Parkinson's disease, which is approximately 2-fold higher than that achieved with amantadine IR dosing (81 mg, equivalent to amantadine HCl 100 mg, administered at 8:00 AM and 4:00 PM, based on prescription data, which indicated that ∼85% of patients with Parkinson's disease treated with amantadine IR were prescribed a dose of #161 mg/day) (Navarro et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Improvements in continuous delivery of amantadine would provide a smooth PK profile achieving high concentrations and better coverage throughout the day compared with the peaks and troughs associated with bolus dosing. As reported in the study by Hauser et al (2018), ADS-5102 can be dosed once daily at bedtime to achieve high morning and sustained daytime amantadine plasma concentrations when symptoms of dyskinesia occur. PK modeling suggested the recommended daily ADS-5102 dosage (274 mg once daily at bedtime) provided maximum steady-state concentrations of ∼1500 ng/ml in patients with Parkinson's disease, which is approximately 2-fold higher than that achieved with amantadine IR dosing (81 mg, equivalent to amantadine HCl 100 mg, administered at 8:00 AM and 4:00 PM, based on prescription data, which indicated that ∼85% of patients with Parkinson's disease treated with amantadine IR were prescribed a dose of #161 mg/day) (Navarro et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…All of these ADLs are known to be affected by the parkinsonian state. Since UDysRS Part 1B instructs a patient to rate the impact of "jerking or twisting movements" occurring "when your Parkinson's disease medications were working" [22], the findings show that the ADLs are specifically worsened by dyskinesia in its typical forms.…”
Section: Discussionmentioning
confidence: 99%
“…It is the only medication approved by the United States Food and Drug Administration for this use [21]. ADS-5102 dosed at bedtime provides high plasma amantadine concentrations upon waking and throughout the day, with lower concentrations in the evening [22]. In dyskinetic PD patients, both of two pivotal phase 3 clinical trials of ADS-5102 (EASE LID [23] and EASE LID 3 [24]) demonstrated a reduction of dyskinesia, as measured by the primary endpoint (total score at Week 12 on the Unified Dyskinesia Rating Scale, the UDysRS [25,26]).…”
Section: Introductionmentioning
confidence: 99%
“…ADS‐5102 (amantadine) extended release capsules (GOCOVRI™), a novel formulation of amantadine, were designed to deliver a distinct concentration‐time profile of amantadine that is not achievable with amantadine IR. With bedtime dosing of ADS‐5102, its initial slow rise in plasma concentration overnight achieves twice the plasma level (∼1500 ng/mL) of a standard dose of amantadine IR, 100 mg bid during the early morning and throughout the day . The once‐daily dosing regimen of ADS‐5102 may also provide enhanced convenience compared with multiple dosing of amantadine IR.…”
Section: Introductionmentioning
confidence: 99%
“…With bedtime dosing of ADS-5102, its initial slow rise in plasma concentration overnight achieves twice the plasma level (1500 ng/mL) of a standard dose of amantadine IR, 100 mg bid during the early morning and throughout the day. 19 The once-daily dosing regimen of ADS-5102 may also provide enhanced convenience compared with multiple dosing of amantadine IR.…”
Section: Introductionmentioning
confidence: 99%